Operative hysteroscopy intravascular absorption syndrome is more than just the gynecological transurethral resection of the prostate syndrome: A case series and literature review - Ming-Tse Wang; Chuen-Chau Chang; Ming-Hui Hsieh; Ching-Wen Chang; Yu-Hsuan Fan Chiang; Hsiao-Chien Tsai (Elsevier, 2020)
Objective: Operative hysteroscopy intravascular absorption (OHIA) syndrome refers to fluid overload complications from operative hysteroscopies. Despite guidelines for safe operative hysteroscopies, instances of OHIA syndrome have been reported. Case report: We reported three cases of OHIA syndrome. A 48-year-old female patient presented net irrigation fluid of 11,900 mL and developed severe metabolic acidosis, conscious disturbance, acute pulmonary edema, and unexpected intensive care unit admission. A 49-year-old female patient presented net irrigation fluid of 4500 mL and developed desaturation and acute pulmonary edema. A 45-year-old female patient presented net irrigation fluid of 2400 mL and developed hyponatremia, increased hilum lung marking, and prolonged postanesthesia care unit observation. Conclusion: For safety, clinicians should use isotonic electrolyte-containing distension media and bipolar electrosurgical instruments in operative hysteroscopies, and fluid status should be monitored closely, particularly at net and total irrigation amounts >3000 and > 8000 mL, respectively. Intrauterine pressure should also be minimized to reduce intravascular and intraperitoneal absorption.